The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/1980-265x-tce-2020-0103
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Sociodemographic and Reproductive Characteristics on Reproductive Autonomy Among Women

Abstract: Objective to analyze the influence of the sociodemographic and reproductive characteristics on reproductive autonomy among women through the subscales of the Reproductive Autonomy Scale. Method an analytical and cross-sectional study with a stratified sample composed of 346 female rural workers registered in Chapéu de Palha Mulher Program in Pernambuco. Data collection occurred in the month of February 19th and February 23rd, 2018. The National Health Survey questionnaire and the Reproductive Autonomy Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 23 publications
(44 reference statements)
0
5
0
3
Order By: Relevance
“…As limitações desta pesquisa decorrem das características do método epidemiológico escolhido, uma vez que a coleta de dados sobre exposição e desfecho ocorre em um único momento no tempo, não permitindo inferir causalidade entres as variáveis e os desfechos. Outro desafio foi a comparabilidade dos achados, por serem identificados poucos estudos na literatura utilizando a Escala de Autonomia Reprodutiva (3,10,12,14,19,29) . Isso resultou em limitação na comparabilidade dos resultados deste estudo com os encontrados na literatura.…”
Section: Limitações Do Estudounclassified
See 1 more Smart Citation
“…As limitações desta pesquisa decorrem das características do método epidemiológico escolhido, uma vez que a coleta de dados sobre exposição e desfecho ocorre em um único momento no tempo, não permitindo inferir causalidade entres as variáveis e os desfechos. Outro desafio foi a comparabilidade dos achados, por serem identificados poucos estudos na literatura utilizando a Escala de Autonomia Reprodutiva (3,10,12,14,19,29) . Isso resultou em limitação na comparabilidade dos resultados deste estudo com os encontrados na literatura.…”
Section: Limitações Do Estudounclassified
“…A concretização de fato sobre a autonomia reprodutiva da mulher aponta a importância de se aprofundar a discussão, principalmente, voltada para grupos populacionais com maior vulnerabilidade socioeconômica e cultural, como é o caso das mulheres nas regiões rurais que apresentam perfil ainda marcado pela ideologia patriarcal, desigualdades de gênero e poder (12) . Apesar de serem encontrados estudos internacionais sobre autonomia reprodutiva, a relevância desta pesquisa se dá também pela escassez de estudos nacionais utilizando este tema, na medida que foram localizados apenas cinco artigos brasileiros (9)(10)(12)(13)(14) . Deste modo, o estudo tem como questão de pesquisa: as características sociodemográficas e reprodutivas das trabalhadoras rurais estão associadas à sua autonomia reprodutiva?…”
Section: Introductionunclassified
“…The limitations of this research stem from the characteristics of the epidemiological method chosen, since data collection on exposure and outcome occurs at a single moment in time, not allowing to infer causality between variables and outcomes. Another challenge was the comparability of the findings, because few studies are identified in the literature using the Reproductive Autonomy Scale (3,10,12,14,19,29) . This resulted in a limitation in the comparability of the results of this study with those found in the literature.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The realization of a fact about women's reproductive autonomy points to the importance of deepening the discussion, mainly focused on population groups with greater socioeconomic and cultural vulnerability, as is the case of women in rural regions, whose profile is still marked by patriarchal ideology, gender and power inequalities (12) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation